Sistem Pencarian Kata Bahasa Indonesia Berbasis Awalan (Prefix Search) Menggunakan Python - Alhafiz Okliano Hardianta; M.Radit Qoiri Hasibuan; M.Wira Adithya; Muhammad Rafly Solihin; Dila Handayani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research develops a prefix-based Indonesian word search system using the Python 3.11 programming language. This system allows users to type the initial portion of a word, then displays all matching words from the KBBI digital dictionary. The program's main feature is the gradual display of results, allowing users to view long word lists comfortably and interactively. The program is modular using several functions, making it easy to develop additional features such as auto-correct or integration with other text applications. Test results show that the system is able to display matching words quickly and accurately, and facilitates correct word spelling..